Republic, villages and municipalities in Piura, 19th century. The political experience of Morropon and Chulucanas - Espinoza Claudio, César (2010)
The main objective of this article is to explain the essencial role that played the municipalities of Morropón and Chulucanas for the consolidation of the populated centres inside Morropón and Yapatera large states. It also makes an effort to expose the protagonism of municipalities’ leadership handling a political and juridical culture, and fighting for the hegemony and power against Arrese family in a time of construction of state and republic in Piura’s region in the 19th century. Consulting manuscript sources of Piura’s Regional Archive and the Congress of the Republic we try to confront the beliefs and speeches and face them up with the historical reality of a region in a development process, and to include the political logic of these agglomerations of rural colonists, black freedmen, half-caste and Creole smallholders that have migrated and suited in these urban groups that later would reach the categories of hamlets, villages, towns, and the capitals of districts and provinces.